Case report: Urethra prolapse in an English Bulldog breed canine (Revista Sistemas de Producción Agroecológicos, 2023)
Urethral prolapse in dogs is a rare pathology that affects young dogs of brachycephalic breeds; The young English Bulldog is the most frequently affected. This disease is characterized by the protrusion of the urethral mucosa at the tip of the penis and owners often notice excessive licking accompanied by bleeding. Urethral prolapse is not common, it can occur after excessive sexual excitement or masturbation, it can also be associated with genitourinary infections or be congenital. In this case, the patient entered the veterinary clinical center of the University of Los Llanos, because he had bleeding in the penis, a physical examination was performed and urethral prolapse was detected, which was responsible for the penile hemorrhagic crisis. , urgency for which it is decided to intervene surgically and apply the Urethropexy technique, including Orchiectomy as part of the preventive treatment. After the surgical process, the patient recovers satisfactorily and is discharged.
Keywords: Animal disease; Animal genetics; Orchiectomy; Sexual behavior; Urethropexy